2001
DOI: 10.1161/01.atv.21.4.489
|View full text |Cite|
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Transactivation by Angiotensin II Requires Reactive Oxygen Species in Vascular Smooth Muscle Cells

Abstract: Abstract-Angiotensin II (Ang II) is a vasoactive hormone with critical roles in vascular smooth muscle cell growth, an important feature of hypertension and atherosclerosis. Many of these effects are dependent on the production of reactive oxygen species (ROS). Ang II induces phosphorylation of the epidermal growth factor (EGF) receptor (EGF-R), which serves as a scaffold for various signaling molecules. Here, we provide novel evidence that ROS are critical mediators of EGF-R transactivation by Ang II. Pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
199
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(215 citation statements)
references
References 37 publications
16
199
0
Order By: Relevance
“…Indeed, disruption of the actin cytoskeleton and its associated focal adhesions with cytochalasin D completely inhibits Ang II-, but not EGF-, induced EGF-R phosphorylation. 2 This result supports the concept that an intact cytoskeleton and/or focal adhesions are required for Ang II-induced transactivation of the EGF-R, in VSMCs. The colocalization of activated EGF-Rs, paxillin and tyrosine-phosphorylated caveolin suggests that in focal adhesions, phosphorylated caveolin may function as a positive regulator for transactivation and may be relevant to the generation of active, spatially organized signaling molecules.…”
Section: Fig 2 Effect Of Cholesterol-binding Agents On Egf-r Phosphsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, disruption of the actin cytoskeleton and its associated focal adhesions with cytochalasin D completely inhibits Ang II-, but not EGF-, induced EGF-R phosphorylation. 2 This result supports the concept that an intact cytoskeleton and/or focal adhesions are required for Ang II-induced transactivation of the EGF-R, in VSMCs. The colocalization of activated EGF-Rs, paxillin and tyrosine-phosphorylated caveolin suggests that in focal adhesions, phosphorylated caveolin may function as a positive regulator for transactivation and may be relevant to the generation of active, spatially organized signaling molecules.…”
Section: Fig 2 Effect Of Cholesterol-binding Agents On Egf-r Phosphsupporting
confidence: 86%
“…Several signaling mechanisms have been implicated in Ang II-induced EGF-R transactivation, including calcium and c-Src in VSMCs (2,19). Interestingly, cholesterol depletion had no effect on either of these early signaling events, suggesting that the intact cholesterol-enriched microdomain is not required for the initial activation of calcium and c-Src.…”
Section: Fig 2 Effect Of Cholesterol-binding Agents On Egf-r Phosphmentioning
confidence: 93%
“…We show that submillimolar concentrations of hydrogen peroxide lead to tyrosine phosphorylation and activation of Src or PDK-1, suggesting that these kinases are modulated by ROS. This is in agreement with previous published studies reporting the redox sensitivity of Src and PDK-1 in other cell types (30,43,45,48,53). These observations prompted us to test the hypothesis that endogenous ROS act as upstream intermediates in Ang II-mediated and Src-dependent activation of PDK-1.…”
Section: Discussionsupporting
confidence: 94%
“…14 -16 Previous publications have suggested that ROS produced by NADPH oxidase mediate many angiotensin II effects in the cardiovascular system. 17,18 It was reported recently that Aldo also increases NADPH oxidase activity in the vasculature. 19,20 In the NADPH oxidase system, cytosolic component p47 phox was shown to have a pivotal role in the regulation of enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%